3 Keys to Management Success Profile Strengthening of Pancasila Student Profile (P5) Project In The Implementation of The Independent Curriculum in Indonesia - Fera Maulidya Sukarno (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
The Gong for Implementation of the Independent Curriculum has been beaten. All elements of education are enthusiastic about exploring the new spirit of 'Freedom to Learn'. The National Education Vision places the dimensions and elements of the Pancasila Student Profile as a goal. This is seriously affirmed in the Implementation of the Independent Curriculum through the co-curricular activities of the Strengthening Pancasila Student Profile Project (P5), whose existence has received the spotlight. However, a fundamental problem was found, namely the teachers' lack of understanding regarding the implementation of P5, which was considered quite complicated. Given the urgency of P5 in the Implementation of the Independent Curriculum, as a lesson learner, an assessment was made of the management of P5 at SMPN 1 Subang through a case study research method with an embedded single-case design, which reveals a linear-analytic, chronological, theory-based, and comparative analysis of how is the management of P5 on the first theme and the second theme that is currently running. Data was collected using qualitative and quantitative instrumentation, then analyzed descriptively. As a result, patterns can be mapped, and several strategies are the key to the successful management of P5: Teacher collaboration, Differentiated Learning, and Strategic Partnerships.